Risk, Return, and Equilibrium: A General Single-Period Theory of Asset Selection and Capital Market Equilibrium (Book). - Porter, R. Burr; Sterling, Robert R. (The Accounting Review, 1971)
Abstract Reviews the book "Risk, Return, and Equilibrium: A General Single-Period Theory of Asset Selection and Capital-Market Equilibrium," by Bernell Kenneth Stone.